Medčasovna analiza čezmejnih stikov prebivalcev Monoštra s sosednjo Slovenijo - Mejak, Renata (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2001)
Among the different sources shaping the image of Slovenes and of life in Slovenia, respondents from Monoster ascribed greatest significance to direct personal contacts, i.e. visits to Slovenia.The number of visits to Slovenia isincreasing year by year due to unimpeded crossing of the state border, the opening of border crossings in the Porabje, and good neighbourly relations between Slovenia and Hungary. At the same the number of respondents that have not yet visited Slovenia is constantly diminishing. Most of the visits to Slovenia are of accidental nature.The main obstacles to visiting Slovenia are unfavourable financial situation, lack of language command, bad traffic connections between Monoster (and the Porabje) and Slovenia by means of publictransportation, distance from border crossings, high prices in Slovenia,old age and the lack of time.
Keywords: Hungary; Madžarska; Porabje; Slovenci; Slovenes; narodne manjšine; etnični odnosi; obmejna območja; obmejno sodelovanje